How to Fuck a Kraken: Cephalopod Sexualities and Nonbinary Genders in eBook Erotica - Van Engen, Dagmar (Humanimalia, 2017)
Recent theories in posthumanism and animal studies have shown how race, gender, and sexuality help constitute the boundaries of the human and the animal as such. This essay argues that vertebrate land animals have most frequently formed the basis for racialized human-animal comparisons and the gender-sexual paradigms that underwrite them, and proposes instead a turn to invertebrate sea animals. In speculative fiction, these alien creatures offer a more complex interface for the racialized gender and sexual registers of human-animal imaginaries. In particular, erotic monster fiction by Alice Xavier recasts the meaning of animality as a figure of the erotic by transforming octopi and anemones into nonbinary-gendered objects of human desire. If animality is a crucial figure for how humans imagine animals in order to reimagine ourselves, then Alien Seed’s fantasies about invertebrate animals create more space for trans and nonbinary genders in ways deeply entangled with the nonhuman world.